MARINA - (:unkn) unknown (My University, 2026)
May 2013 - June 2014: Participation in the European funded project: MARINA Platform (MARINA), CP-IP 62305700 (http://www.marina-platform.info/) focused at the establishment of a set of equitable and transparent criteria for the evaluation of multi-purpose platforms for marine renewable energy.